Perspectives and problems of the development of accounting in the terms of using Big Data - S.F.; O.M. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The need to transform the accounting system in the context of the transition to Industry 4.0 has been grounded. The essence and role of Big Data in improving enterprise management systems have been revealed. The problem of transformation of the current accounting practice under the influence of Big Data technologies has been outlined. Areas of using Big Data in the accounting system have been highlighted. The areas of improvement of methodical aspects of accounting with the help of Big Data tools have been characterized. The advantages of using the concept of Big Data in accounting have been analyzed. The role of Big Data in expanding the analytical functions of accountants has been highlighted. The expediency of professional hybridization of accountants in the context of using Big Data tools has been grounded. The peculiarities of the impact of Big Data on the improvement of the organization of the accounting system have been determined. The advantages of using Big Data analytics to improve the productivity of accounting personnel have been analyzed. The risks and problems of using Big Data in the accounting system have been characterized.